PELATIHAN LANSIA BEBAS NYERI LUTUT DI PATUKAN AMBARKETAWANG KECAMATAN GAMPING KABUPATEN SLEMAN - Yoni Astuti; Triwulandari Kesetyaningsih; Ambar Relawati (Universitas Jenderal Soedirman, 2020)
The increasing of Indonesian life expectancy needs to be balanced with the ability of independence in the health aspect of the elderly community. Patukan Ambarketawang Yogyakarta has high in a number of elderly people. Knee pain experienced by the elderly, which have an impact on reducing their activity and productivity. Isoquadrisep exercises are one of the non-pharmacological efforts that are recommended to prevent knee pain. Elderly Posyandu in Patukan Ambarketawang Gamping Sleman village conducts routine activities to control the health of the elderly in general such as to measure blood pressure. Posyandu cadres and elderly participants are not familiar with isoquadrisep exercises on the knee to reduce knee pain in the elderly. Community partnership service is carried out to form cadres and isoquadrisep exercise training to prevent elderly with knee pain. The method for this activity is Training Of Trainer on quadriceps exercise for cadres and some communities. The results of this activity are cadres have an isoquadricep exercise agenda at each elderly meeting alternating with other exercises that already existed in Patukan Ambarketawang Gamping.